A demographic ménage à trois: interactions between disturbances both amplify and dampen population dynamics of an endemic plant. (23rd August 2016) - Tye, Matthew R.; Menges, Eric S.; Weekley, Carl; Quintana‐Ascencio, Pedro F.; Salguero‐Gómez, Roberto
Summary: Natural and anthropogenic disturbances co‐occur in most systems, but how they interact to shape demographic outcomes remains poorly understood. Such interactions may alter dynamics of populations in non‐additive ways, making demographic predictions challenging when focusing on only one disturbance. Thus, understanding the interactive effects of such disturbances is critically important to determine the population viability of most species under a diversity of stressors. We used a hierarchical integral projection model (IPM), parameterized with 13 years of field data across 20 populations, encompassing 2435 individuals of an endangered herb, Liatris ohlingerae . We examined interactive effects of vertebrate herbivory, fire and anthropogenic activities (sand roads) on vital rates (e.g. survival, growth, reproduction, recruitment) and ultimately on population growth rates (λ), to test the hypothesis that interactions amplify or dampen differences in λ depending on environmental contexts. We constructed megamatrices to determine coupled dynamics in individuals damaged vs. not damaged by herbivores in roadsides and in Florida scrub with different times since fire. We identified strong interactive effects of fire with herbivory and habitat with herbivory on vital rates and on population growth rates in the IPM model. We also found different patterns of variation in λ between habitat and time‐since‐fire scenarios; population growth rates were higher in roadside populations compared to scrub populations and declined with increasing time since fire. Herbivory had interactive effects with both fire and human disturbances on λ. Herbivory resulted in decreased differences in λ due to anthropogenic disturbance and slightly increased differences in λ due to time since fire. Synthesis . The co‐occurrence of various disturbances may both amplify and dampen the effects of other disturbances on population growth rate, thus shaping complex population dynamics that are neither linear nor additive. These realistic nonlinearities represent challenges in understanding and projecting of population dynamics. Here, we examined the effects of various sources of disturbance on the population dynamics of an endangered plant species, finding complex interactions affecting population growth rates. We argue that integration of multiple, interacting stressors in IPMs will allow more accurate estimation of the overall effects of ecological processes on species viability. Abstract : The co‐occurrence of various disturbances may both amplify and dampen the effects of other disturbances on population growth rate, thus shaping complex population dynamics that are neither linear nor additive. These realistic nonlinearities represent challenges in understanding and projecting of population dynamics. Here, we examined the effects of various sources of disturbance on the population dynamics of an endangered plant species, finding complex interactions affecting population growth rates. We argue that integration of multiple, interacting stressors in IPMs will allow more accurate estimation of the overall effects of ecological processes on species viability.